Analysis Of The Characterization Of Abdullah In The Novel “Na’am Ahwãka” By Marwah Mamdouh (Structuralism Study): Taḥlīl Taṣwīr Shakhsiyyat ʿAbd Allāh fī Riwāyat "Naʿam Ahwãka" li-Marwā Mamdūḥ (Dirāsah Bināwiyyah) - Binti Khalid, Khaleeda Iman; Syarifuddin; Zulhelmi; Sumardi (An-Nahdah Al-'Arabiyah, 2025)
This research examines the character of Abdullah in the novel Na’am Ahwãka by Marwah Mamdouh using a structuralism approach. The study employs a qualitative descriptive method, analyzing written data from the novel through note-taking and literature review. The analysis focuses on identifying, classifying, and interpreting Abdullah’s character traits to understand his role in the story. The novel Na’am Ahwãka explores themes of love and resilience, with Abdullah serving as a key figure who complements the main character, Rana. Through the structuralism approach, this research highlights Abdullah’s contribution to the narrative’s overall structure and meaning. The findings reveal that Abdullah embodies five characters: caring, optimistic, entertaining, loyal, and concerned. يبحث هذا البحث في شخصية عبد الله في رواية "نعم أهواك" لمروة ممدوح باستخدام منهج البنيوية. تعتمد الدراسة على المنهج الوصفي النوعي، حيث يتم تحليل البيانات المكتوبة من الرواية من خلال تدوين الملاحظات ومراجعة الأدبيات. يركز التحليل على تحديد وتصنيف وتفسير سمات شخصية عبد الله لفهم دوره في القصة. تتناول رواية "نعم أهواك" موضوعات الحب والصمود، حيث يُعد عبد الله شخصية رئيسية تُكمل البطلة رنا. ومن خلال النهج البنيوي، يبرز هذا البحث مساهمة عبد الله في البنية العامة والسياق الدلالي للرواية. تكشف النتائج أن عبد الله يجسد خمس سمات أساسية: العناية، والتفاؤل، والتسلية، والوفاء، والاهتمام. Penelitian ini mengkaji karakter Abdullah dalam novel Na’am Ahwãka karya Marwah Mamdouh dengan menggunakan pendekatan strukturalisme. Penelitian ini menggunakan metode deskriptif kualitatif dengan menganalisis data tertulis dari novel melalui teknik pencatatan dan tinjauan pustaka. Analisis difokuskan pada identifikasi, klasifikasi, dan interpretasi sifat-sifat karakter Abdullah untuk memahami perannya dalam cerita. Novel Na’am Ahwãka mengeksplorasi tema cinta dan ketabahan, dengan Abdullah sebagai tokoh penting yang melengkapi karakter utama, Rana. Melalui pendekatan strukturalisme, penelitian ini menyoroti kontribusi Abdullah terhadap struktur dan makna keseluruhan narasi. Hasil penelitian menunjukkan bahwa Abdullah memiliki lima sifat utama: penyayang, optimis, penghibur, setia, dan peduli.